Amine‐Functionalized Spin Crossover Building Blocks. Issue 43 (12th September 2019) - Flötotto, Henrik; Secker, Tim; Kögerler, Paul; Besson, Claire
Abstract : Bistable spin crossover complexes such as [Fe{HB(pz)3 }2 ] (pzH = pyrazole) show promise for sensor applications and electrically‐controlled data storage units, but exploiting their potential hinges on their integration into a functional environment. We here present a system enabling such covalent post‐functionalization steps in both symmetric and asymmetric patterns, based on the amine‐functionalized complex [Fe{HB(4‐NH2 pz)(pz)2 }2 ], obtained by reduction of the nitro analogue. The building block aspects of [Fe{HB(4‐NH2 pz)(pz)2 }2 ] are showcased by its transformation into amide, imine and azo derivatives, which are structurally and magnetically characterized. All tris(pyrazolyl)borate complexes retain the spin crossover properties of their parent compound, with spin crossover temperatures ranging from 350 to 430 K. The transition parameters are correlated with the electronic properties of the functionalizing group, opening the possibility of fine‐tuning the spin crossover properties of the building block as it is integrated in the environment of choice. Abstract : An amine‐functionalized spin crossover building block based on a Fe II tris(pyrazolyl)borate core reacts to form amide, imine, and azo derivatives without loss of magnetic bistability. Controlled pyrazole metathesis allows for symmetric and asymmetric incorporation of nitro groups used as precursor for the amine.